Globalization and The Future Hope for Christianity: How Africa Can Shape World Christianity - Seth Ahmetmu Biwul (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2025)
Religion has not been insulated from the widespread forces of globalization. While these forces have facilitated the transmission of religion from one region to another, they have also reshaped the face of religion in various parts of the world. Focusing on the Christian faith in Africa—particularly Nigeria—this paper argues that globalization has functioned as an effective means of transporting Western religious ideals into the Global South. Consequently, globalization is viewed with suspicion as a tool of westernization, a concern reinforced by the marginalization of African Christian music and culture within the Global North. Yet, with Christianity’s imminent demographic shift to the Global South, it is imperative for the region to reclaim ownership of its faith and resist Western distortions. To this end, the paper reviews Western influence on contemporary Christianity, analyzes the deceptive aspects of globalization, and suggests ways in which African Christianity can actively engage globalizing forces, leveraging them to transmit African Christian norms and values back to the Global North.